Transcriptional regulation of the virulence genes and the biofilm formation associated operons in Vibrio parahaemolyticus - Yiquan Zhang; Yue Qiu; Xingfan Xue; Miaomiao Zhang; Junfang Sun; Xue Li; Lingfei Hu; Zhe Yin; Wenhui Yang; Renfei Lu; Dongsheng Zhou (Gut Pathogens, 2021)
Abstract Background The membrane fusion protein (mfp) gene locus of Vibrio parahaemolyticus consists of two operons, cpsQ-mfpABC and mfpABC, which are both required for biofilm formation. ToxR and CalR are required for the full virulence of V. parahaemolyticus, and their mutual regulation has been demonstrated. Moreover, cell density-dependent expression of toxR was previously observed in V. parahaemolyticus, but details about the related mechanisms remained unclear. QsvR can work with the master quorum sensing (QS) regulators AphA and OpaR to regulate virulence expression and biofilm formation. Results In the present work, we showed that QsvR bound to the promoter-proximal DNA regions of toxR and calR to repress their transcription as well as occupying the regulatory regions of cpsQ-mfpABC and mfpABC to activate their transcription. Thus, we reconstructed the QsvR-dependent promoter organization of toxR, calR, cpsQ-mfpABC, and mfpABC. Conclusion QsvR directly repressed toxR and calR transcription as well as directly activated cpsQ-mfpABC and mfpABC transcription. The data presented here promotes us to gain deeper knowledge of the regulatory network of the mfp locus in V. parahaemolyticus.